Understanding innovation. Innovation education – a students’ perspective - Sołek-Borowska, Celina (Zrozumieć innowacje. Innowacyjna edukacja – perspektywa studentów, 2018)
The author of this research offer the hypothesis that university education is the most important condition for the development of an innovation-oriented economy and that the creation of an innovation society requires the modernization of university education. Innovation education has been identified as a key contributor to the enhancement of the innovative behavior of individuals, organizations and economies. It is widely believed that countries’ social and economic well-being will depend to an ever greater extent on the quality of their citizens’ education: the emergence of the so-called ‘knowledge society’, the transformation of information and the media, and increasing specialization on the part of organizations, all of which call for high skill profiles and levels of knowledge. This study builds to examines an individual’s understanding of the term innovation. By looking at undergraduate and postgraduate students in Poland represented by the Warsaw School of Economics it is hoped to ascertain what role education plays in developing the notion of “innovation” and innovation education with the purpose of assessing it
Informatyka Ekonomiczna = Business Informatics, 2018, Nr 1 (47), s. 85-96
Keywords: innovation; innovation education; university education; innowacja; edukacyjna innowacja; wykształcenie wyższe